FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PETUGAS PEMADAM KEBAKARAN DI WILAYAH KABUPATEN KAMPAR TAHUN 2018 - Yusmardiansah Yusmardiansah Yusmardiansah; Nur Azma Azma (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
One job that has a high risk is firefighters. In carrying out their duties, firefighters must use personal protective equipment in accordance with the needs at the scene to avoid the risk of accidents or health problems. The purpose of this study was to determine the factors associated with the use of personal protective equipment in firefighters in Kampar District. This research was conducted on September 13-16, 2018. This research used a quantitative analytic survey method with cross sectional method. The sample of this study were 45 people, with a total sampling technique. Data were analyzed univariately and bivariately with the Chi-Square test and Fisher's Exact Test. The results of this study are that there is a significant relationship between knowledge with the use of PPE obtained p value (0.002)